2020
DOI: 10.1002/ijgo.13124
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and key predictors of perinatal depression among postpartum women in Ghana

Abstract: Objective:To determine the prevalence and key predictors of perinatal depression among women in Accra. Method:A two-step hospital-based cross-sectional study from May to July 2016.Patient Health Questionnaire version 9 was administered to postpartum mothers, and those aged 18 years or older with scores above 5 who delivered at LEKMA, Ridge, and Korle Bu Hospitals were recruited. A modified Edinburgh Postnatal Depression Scale was used to assess depression at 2 weeks postpartum. Associations between perinatal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
10
1
1
Order By: Relevance
“…[16][17][18] A typical case is noted by Saeed et al, whose assessment of depression among mothers of children under five months in the Bole district revealed a 16.8% prevalence rate. 16 A multitude of biological, psychological, and social factors have been found in previous studies to be linked to the development of PPD. 19,20 Poverty, lack of social support, intimate partner violence, a history of pregnancy loss, and unintended pregnancy, all of which are common in LMICs, are risk factors for PPD.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…[16][17][18] A typical case is noted by Saeed et al, whose assessment of depression among mothers of children under five months in the Bole district revealed a 16.8% prevalence rate. 16 A multitude of biological, psychological, and social factors have been found in previous studies to be linked to the development of PPD. 19,20 Poverty, lack of social support, intimate partner violence, a history of pregnancy loss, and unintended pregnancy, all of which are common in LMICs, are risk factors for PPD.…”
Section: Introductionmentioning
confidence: 90%
“…In Ghana, the country‐specific prevalence was 7% 15 . Several studies within the country have reported higher prevalence rates than the national average 16‐18 . A typical case is noted by Saeed et al, whose assessment of depression among mothers of children under five months in the Bole district revealed a 16.8% prevalence rate 16 …”
Section: Introductionmentioning
confidence: 98%
“…In Ghana, a recent study conducted in three public hospitals concurrently, namely a primary health facility, a secondary facility, and a tertiary facility using the EPDS found that the prevalence of PD was 8.6%, 31.6%, and 41.1%, respectively [ 36 ]. Although the regular contact between mothers and perinatal HCP may make the obstetric setting ideal for addressing depression, data suggests that there are existence of barriers, and PD remains under-diagnosed and under-treated [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Según la OMS, tiene una prevalencia a nivel mundial de alrededor del 13% y una incidencia entre el 10% a 15% 6,7 . Afecta entre 20% a 40% de las mujeres en países de bajos ingresos y al 15% de mujeres en países de altos ingresos 8 . No existen estudios que describan su prevalencia en Latinoamérica, sin embargo, se han reportado cifras de 22% en países como Chile y de hasta 32,6% en México 9 .…”
Section: Introductionunclassified